Study Life Style dan Intensitas Taks terhadap Tingkat Stress Operator - Liki Tanziliyo, A.; Dasmawati, Yanti (UNIVERSITAS SERAMBI MEKKAH, 2024)
The research instrument used in this research was a questionnaire sheet. The research instruments used in this study included the Pittsburg Sleep Quality Index (PSQI) questionnaire to assess sleep quality, the NASA-Tlx questionnaire to assess workload, and stress levels which were measured using a Likert scale questionnaire. The analysis of this research was carried out using quantitative descriptive statistics, namely measurements carried out to determine lifestyle (X1) and task intensity (X2) on the operator's stress level (Y). So multiple regression analysis will be carried out with Multivariate analysis using (Methodatic Regression Analysis). The research results showed that there was no significant relationship between the lifestyle variables (X1) and task intensity (X2) on the stress level variable (Y). The expected suggestion is that further studies be carried out with operator age characteristics of 35-40 years and the middle age classification is considered the peak period of productivity and experience. Considering that in this study the operator's age was still relatively young, namely 26-28 years. This is thought to affect sleep quality and stress levels as we age. By comparing data from different age groups, companies can develop policies that are more effective in safeguarding operator well-being throughout an operator's career. Apart from that, further research is needed by considering various influencing factors such as psychological factors and quantitative stress level testing tools.